X-band trisection substrate-intergrated waveguide quasi-elliptic filter - Ismail, Alyani; Razalli, Mohammad Shahrazel; Mahdi, Mohd Adzir; Raja Abdullah, Raja Syamsul Azmir; Noordin, Nor Kamariah; A. Rasid, Mohd Fadlee (EMW Publishing, 2008)
A narrowband trisection substrate-integrated waveguide elliptic filter with coplanar waveguide (CPW) input and output ports is proposed and demonstrated for X-band applications. The filter is formed by incorporating metallized vias in a substrate (RT/Duroid) to create cross-coupled waveguide resonators. The result is an attenuation pole of finite frequency on the high side of the passband, therefore exhibiting asymmetric frequency response. The fabricated trisection filter with a centre frequency of 10.05 GHz exhibits an insertion loss of 3.16 dB for 3% bandwidth and a return loss of -20 dB. The rejection is larger than 15 dB at 10.37 GHz.